Anisotropic mechanical properties of a 3D printed nickel aluminum bronze - Too, Eugene Yun Quan (Nanyang Technological University, 2022)
Metal Alloys such as nickel aluminium bronze (NAB) is applied extensively in autonomous and marine industries e.g., ship piping, valves, and propellers. The material is used for their outstanding properties such as high strength and good ductility. With the good resistance against corrosion, it is considered an ideal material to use in seawater conditions which is beneficial towards marine components. These components are usually produced through different machinery to ensure good performance and ensured that the complexity of the shape being reached. As technology advancement throughout the years, different machines with similar performance are created to ensure the production line becomes faster and smoother. Three-dimensional (3D) printing is one of the methods that create complex shape with high precision and takes lesser production time. In this report, nickel aluminium bronze alloy is being used for investigation of the anisotropic mechanical properties after 3D printing. The material will be used to print out specimens in different direction and whether the microstructure will be affected by the printing patterns. The report will attain information from published journal articles and books to draw comparison between 3D printing and machinery equipment to determine if the 3D printed specimens will be the other alternative to produce components used in marine industries. NAB provides us the opportunity to prolong the life of the components and making good use of the material will ease the maintenance and the lifetime. The experimental results will allow the readers to have a better understanding on whether 3D-printed metal parts could be used in marine and offshore applications.